Content and Face Validation of Educational Infographics for Electronic Cigarette Cessation Among Malaysian Youth - Phoa, Picholas Kian Ann; Halim, Jonathan Wiguna; Wong, Yin How; Naidu, Charles Sharma; Hii, John Ing Kieng; Mohd Fadzil, Faisal Athar; Mohd Azizi, Nurlaili; Wee, Lei Hum (Malaysian Journal of Medical Sciences, 2025)
The increasing prevalence of electronic cigarette (e-cigarette) use among Malaysian youths highlights the inadequacy of current health education initiatives in addressing cessation challenges. This study aims to evaluate the content and face validity of educational infographics to support e-cigarette cessation among youth e-cigarette users in Malaysia. This study employed a cross-sectional study design and involved experts and youth e-cigarette users. Upon the development, 17 experts specialising in smoking or e-cigarette cessation, with a mean age of 39.10 years and a mean years of experience of 12.24 years, were recruited for content validation. Meanwhile, for the face validation, 10 Malaysian youth e-cigarette users, with a mean age of 24.00, were purposively selected to assess the clarity of the infographics and provide feedback. Content validity indices (CVI) and face validity indices (FVI) were calculated for each topic, with thresholds of > 0.74 and 0.83 indicating acceptable content. The infographics demonstrated strong content and face validity, with average CVI of 0.98 (range: 0.94, 1.00; 95% CI: 0.95, 1.00) and average FVI of 0.96 (range: 0.70, 1.00; 95% CI: 0.87, 1.00), respectively. The infographics can be utilised to promote e-cigarette cessation after the trial and implementation phase, to assess their real-world effectiveness.